2015
DOI: 10.4171/emss/11
|View full text |Cite
|
Sign up to set email alerts
|

Flux-saturated porous media equations and applications

Abstract: The aim of this paper is to review the main recent results about the dynamics of nonlinear partial differential equations describing flux-saturated transport mechanisms, eventually in combination with porous media flow and/or reactions terms. The result is a system characterized by the presence of wave fronts which move defining an interface. This can be used to model different process in applications in a variety of areas as developmental biology or astrophysics. The concept of solution and its properties (we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 94 publications
(321 reference statements)
0
66
0
Order By: Relevance
“…Then, exploring or modeling new nonlinear transport/diffusion phenomena is an interesting subject not only from the viewpoint of applications, but also from a mathematical perspective. In the framework of flux-saturated mechanisms, traveling waves have been studied in [15,14,17,18]. In this context, as we will show, the Keller-Segel system with flux-saturated mechanism (5), which is the object of study in this paper, exhibits new properties with respect to the classical one.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…Then, exploring or modeling new nonlinear transport/diffusion phenomena is an interesting subject not only from the viewpoint of applications, but also from a mathematical perspective. In the framework of flux-saturated mechanisms, traveling waves have been studied in [15,14,17,18]. In this context, as we will show, the Keller-Segel system with flux-saturated mechanism (5), which is the object of study in this paper, exhibits new properties with respect to the classical one.…”
Section: Introductionmentioning
confidence: 87%
“…Because of the symmetry of the function G, we deduce that it is necessarily satisfied υ − = υ + := υ ± . Then, we obtain the following result: σt) is an entropic solution on the frame [14,15], then its derivative must be a Radon measure on the support. If we assume that this support is finite, then it can be shown that it is one of those obtained previously.…”
Section: Traveling Wavesmentioning
confidence: 94%
See 3 more Smart Citations